GAME TECHNOLOGIES IN TEACHING WORD FORMATION OF THE RUSSIAN LANGUAGE TO NON-PHILOLOGY STUDENTS - Нурханова Зульфия Уралевна (European Science Publishing, 2024)
The article discusses some game technologies used in teaching Russian word formation to non-philology students.
Keywords: Word formation, game technologies, prefixes, suffixes, interfixes, postfixes.